2013
DOI: 10.1099/mic.0.066910-0
|View full text |Cite
|
Sign up to set email alerts
|

Complementation of a stable Met2-1 mutant of the zygomycete Absidia glauca by the corresponding wild-type allele of the mycoparasite Parasitella parasitica, transferred during infection

Abstract: Compared with prokaryotes, where horizontal gene transfer events are frequently found and can be studied in the laboratory at the mechanistic level, few systems are known that allow direct experimental access to parasexual phenomena in eukaryotes. In zygomycetes, a basal lineage of fungi, several mycoparasitic fungi are known that inevitably form a cytoplasmic continuum with their hosts during infection. We provide evidence that, corresponding to the expectation suggested by the morphology of the infection pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…This biotrophic parasitism involves the fusion of specialized hyphal tips with the host A. glauca and other Mucor relatives ( 1 ). The transfer and expression of nuclear genes have been described for several genes involved in amino acid biosynthesis or that confer antibiotic resistance ( 2 , 3 ). After infection, auxotrophic mutants of A. glauca are complemented by their prototrophic counterparts of the parasite.…”
Section: Genome Announcementmentioning
confidence: 99%
“…This biotrophic parasitism involves the fusion of specialized hyphal tips with the host A. glauca and other Mucor relatives ( 1 ). The transfer and expression of nuclear genes have been described for several genes involved in amino acid biosynthesis or that confer antibiotic resistance ( 2 , 3 ). After infection, auxotrophic mutants of A. glauca are complemented by their prototrophic counterparts of the parasite.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Parasitism is thus necessarily linked with unidirectional transport of organelles from the parasite to the host. The transfer and expression of genes residing in nuclei have been verified for antibiotic resistance markers (2) and several genes involved in amino acid biosynthesis (2, 3). In order to initiate the analysis of mitochondrial information after transfer, we sequenced the mitochondrial DNA (mtDNA) of Parasitella parasitica .…”
Section: Genome Announcementmentioning
confidence: 99%
“…Furthermore several species of Mortierella (Mortierallale order) produce trisporoids that can induce sexual responses in Mucor mucedo and Phycomyces blakesleeanus [9]. Recently it has been demonstrated that the recognition between the parasite fungi Parasitella parasitica (Mocuraceae family) and the host Absidia glauca is mediated by trisporoids which are responsible for sexual phenomena [10,11]. Furthermore, evidence for the existence of genes of trisporoids synthesis in Glomus-like fungi (Phylum Glomeromycota) has been reported [12].…”
Section: Open Accessmentioning
confidence: 99%